1990
DOI: 10.1111/j.1439-0485.1990.tb00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Meiofaunal Community Structure and Nematode Diversity in a Lagoonal Ecosystem (Fangataufa, Eastern Tuamotu Archipelago)

Abstract: Mciofaunal asscmblagcs in a scmi-closed Polynesian atoll havc bccn asscssed. High dcnsitics, numerous micro-and mciobcnthic groups. and 62 diversified (H' = 2.64) ncmatoclc spccics occur. As a whole, the lagoonal habitat may be considcrcd as homogcncous, its variability bcing controllcd by oceanic inflows. 0 1000 l O O O m I J Fig. 1. Major watcr circulation and distribution of micro-meiofaunal densities in Fangataufa lagoon. Nb = circle diarncter for 2000 indiv. . crn-2; Cr = coral knoll reef; P = navigable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
4
3
0
Order By: Relevance
“…The richness of the meiofauna was overall comparable to the data available on similar types of habitats and in tropical regions (Gourbault & Renaud-Mornant 1990; Guo et al ., 2008; Semprucci et al ., 2013). The lowest abundances recorded in the Huvadhoo lagoon could be explained by the well-known inverse trend between meiofaunal abundance and depth (Alongi & Pichon, 1988; de Bovée et al ., 1990; Tietjen, 1992; Vincx et al ., 1994; Sommer & Pfannkuche, 2000; Rex et al ., 2006).…”
Section: Discussionsupporting
confidence: 79%
“…The richness of the meiofauna was overall comparable to the data available on similar types of habitats and in tropical regions (Gourbault & Renaud-Mornant 1990; Guo et al ., 2008; Semprucci et al ., 2013). The lowest abundances recorded in the Huvadhoo lagoon could be explained by the well-known inverse trend between meiofaunal abundance and depth (Alongi & Pichon, 1988; de Bovée et al ., 1990; Tietjen, 1992; Vincx et al ., 1994; Sommer & Pfannkuche, 2000; Rex et al ., 2006).…”
Section: Discussionsupporting
confidence: 79%
“…A great richness in nematode genera was also found, and the presence of a remarkable 96 of 123 genera set 'new records' for the archipelago. A notable overlap in generic composition can be observed between the Maldivian nematode assemblage found in this study and those reported for other tropical and even temperate areas (Heip et al 1985;Alongi 1986;Gourbault & Renaud-Mornant 1990;Gourbault et al 1995;Boucher 1997;Ndaro & Ó lafsson 1999;Raes et al 2007). The distribution of some genera across a broad range of different habitats, and even geographically distant areas, not only proves the wide distribution of these taxa, but also the existence of iso-communities that mainly associate with specific sediment grain sizes (Raes et al 2007).…”
Section: Discussionsupporting
confidence: 72%
“…A notable overlap in generic composition can be observed between the Maldivian nematode assemblage found in this study and those reported for other tropical and even temperate areas (Heip et al. 1985; Alongi 1986; Gourbault & Renaud‐Mornant 1990; Gourbault et al. 1995; Boucher 1997; Ndaro & Ólafsson 1999; Raes et al.…”
Section: Discussionsupporting
confidence: 71%
“…Along the Brazilian coast, the diversity of Xyalidae and Chromadoridae richness is well-documented in the literature, with these families occurring in several environments (Venekey et al , 2010). Although Xyalidae has been previously reported as the most dominant family by Gourbault & Renaud-Mornant (1990) in calcareous shore and by Riera et al (2014) at volcanic sediments, Desmodoridae and Chromadoridae were dominant in most of the other oceanic islands studied, especially in those composed by carbonate sediments with medium-coarse sands (Boucher, 1997; Netto et al , 1999a, b, c).…”
Section: Discussionmentioning
confidence: 82%
“…Comparing the dominant families and genera of nematodes there seems to be a pattern in islands with carbonate sediments. In all islands, nematodes associations are dominated by families Desmodoridae, Oncholaimidae, Epsilonematidae and Chromadoridae; the only exception is Fangataufa Atoll (very fine to fine sand) where Xyalidae is the dominant family (Gourbault & Renaud-Mornant, 1990). However, in islands with volcanic sediments, dominance of nematode families changes drastically from locality to locality, thus reinforcing the role of endemic soils, in structuring nematode associations in volcanic sandy beaches.…”
Section: Discussionmentioning
confidence: 99%